Novel dominant MPAN family with a complex genetic architecture as a basis for phenotypic variability. (5th October 2020) - Balicza, Peter; Bencsik, Renata; Lengyel, Andras; Gal, Aniko; Grosz, Zoltan; Csaban, Dora; Rudas, Gabor; Danics, Krisztina; Kovacs, Gabor G.; Molnar, Maria Judit
Abstract : Objective: Our aim was to study a Hungarian family with autosomal dominantly inherited neurodegeneration with brain iron accumulation (NBIA) with markedly different intrafamilial expressivity. Methods: Targeted sequencing and multiplex ligation-dependent probe amplification (MLPA) of known NBIA-associated genes were performed in many affected and unaffected members of the family. In addition, a trio whole-genome sequencing was performed to find a potential explanation of phenotypic variability. Neuropathologic analysis was performed in a single affected family member. Results: The clinical phenotype was characterized by 3 different syndromes—1 with rapidly progressive dystonia-parkinsonism with cognitive deterioration, 1 with mild parkinsonism associated with dementia, and 1 with predominantly psychiatric symptoms along with movement disorder. A heterozygous stop-gain variation in the C19Orf12 gene segregated with the phenotype. Targeted sequencing of all known NBIA genes, and MLPA of PLA2G6 and PANK2 genes, as well as whole-genome sequencing in a trio from the family, revealed a unique constellation of oligogenic burden in 3 NBIA-associated genes ( C19Orf12 p.Trp112Ter, CP p.Val105PhefsTer5, and PLA2G6 dup(ex14)). Neuropathologic analysis of a single case (39-year-old man) showed a complex pattern of alpha-synucleinopathy and tauopathy, both involving subcortical and cortical areas and the hippocampus. Conclusions: Our study expands the number of cases reported with autosomal dominant mitochondrial membrane protein-associated neurodegeneration and emphasizes the complexity of the genetic architecture, which might contribute to intrafamilial phenotypic variability.